From here to there: library content in the digital age - Evans, Wendy (Henry Stewart Talks, 2012)
UK digital content, Academic perspective, Born digital, Cost of accessing digital content, Funding models, E-journals, Access vs. ownership, E-books, Reasons for low take up, Purchasing models, Barriers to accessing digital content, Open access -The future